Local photochemotherapy in chronic hand dermatitis - Wolska, Hanna; Jeziorkowska, Renata (Dermatology Review/Przegląd Dermatologiczny, 2012)
Introduction. Chronic hand dermatitis (CHD) is a common, chronic disease and is associated with significant loss of quality of life. Due to different etiologies, no standard commonly accepted therapy is available. The first-line treatment, topical corticosteroids, is not always fully effective. Recently alitretinoin proved to be very promising therapy for chronic hand dermatitis, however, it is still not readily available. Objective. Presentation of the results of therapy with local PUVA in refractory, long-lasting chronic hand dermatitis. Material and methods. Fifty-four patients (39 females and 15 males) aged from 25 to 75 years with long-lasting (mean 7.7 years) CHD refractory to the previous standard therapy were included. PUVA therapy was performed with orally administered 8-methoxypsoralen (~0.8 mg/ kg) or after topical application of 0.1% Oxsoralen ointment. Irradiated with UVA were only affected body areas (palms/palms and soles). Initial UV doses ranged, depending on the way of psoralen application, from 0.5 J/cm 2 to 1.0 J/cm 2 , and were increased every 2 to 5 irradiations by 0.25 J/cm 2 . The therapy was conducted 3 times a week until a satisfactory result was obtained. Ten patients were additionally treated with acitretin (20-30 mg/day). Results . Complete or almost complete clearing of skin lesions was obtained in 24 patients (44.4%). In a further 15 patients there was observed significant improvement; thus in 48 (88.9%) patients a satisfactory effect of the therapy was noted. Addition of acitretin enabled very good results to be obtained for these patients. Significant side effects were observed only after topical application of psoralen. They corresponded to typical adverse effects of PUVA, i.e. mild to moderate phototoxic reaction, but they did not lead to discontinuation of the therapy. All patients were very happy with the treatment option used. Conclusions. Local PUVA seems, at the moment, the most effective treatment option for chronic hand dermatitis.